Measuring teacher identity during the transition from medical school to residency. Issue 4 (1st October 2020) - Sherman, Stephanie; Kumar, Shelley; Lim, Jonathan; Sargsyan, Zaven; Ratan, Bani; Turner, Teri
Abstract: Residents undergo professional identity formation during training, and the integration of a teacher identity into that of a clinician is part of this process. We aimed to measure the teacher identity of incoming interns of various specialties. In this cross-sectional, survey-based study, we modified a validated teacher identity scale and distributed it to residents attending orientation at a large, academic institution. A total of 297 residents took the survey, including 272 interns; 80% (218/272) of interns completed the survey and permitted use of their data. The mean score for global teacher identity was 4.16 (SD 0.67) on a 1 to 5 Likert scale. There were significant differences between interns' current self-assessed teaching abilities and their desired future performance as teachers ( P < 0.001 for all domains). Male interns had higher global teacher identity scores (4.27) than female interns (4.05; P = 0.02). There were no differences in global teacher identity between interns in medical, surgical, and supportive specialties. Interns who had participated in a student-as-teacher program in medical school had higher global teacher identity ( P < 0.001) than those who had not. In conclusion, teacher identity is high in incoming interns, with higher scores in men and in those who completed student-as-teacher programs in medical school.